2007
DOI: 10.17796/jcpd.32.2.l512r1p807w54582
|View full text |Cite
|
Sign up to set email alerts
|

Microtensile Bond Strength of Contemporary Adhesives to Primary Enamel and Dentin

Abstract: The purpose of this study was to assess bond strength of three self-etching and two total-etch adhesive systems bonded to primary tooth enamel and dentin. Materials and methods: Forty extracted primary human molars were selected and abraded in order to create flat buccal enamel and occlusal dentin surfaces. Teeth were assigned to one of the adhesive systems: Adper Scotch Bond Multi Purpose, Adper Single Bond 2,Adper Prompt L-Pop, Clearfil SE Bond and AdheSE. Imediately to adhesive aplication, a composite resin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
1
20
0
9
Order By: Relevance
“…In present study the difference between SBS of Single Bond 2 and SE Bond was not significant. Some other studies reported similar results [25,26].…”
Section: Discussionsupporting
confidence: 63%
“…In present study the difference between SBS of Single Bond 2 and SE Bond was not significant. Some other studies reported similar results [25,26].…”
Section: Discussionsupporting
confidence: 63%
“…As the chemical, morphological, and physiological aspects vary between permanent teeth and deciduous teeth (Mortimer, 1970;Sonju-Clasen and Ruyter, 1997), the behavior of primary teeth seems to be different under conditions such as caries, erosion process, and bond strength (Hunter et al, 2000;Marquezan et al, 2008;Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have shown higher bond strength and lower marginal leakage of these bonding agents in primary teeth. [33][34][35] The results of present study showed no statistically significant differences between the mean of the shear bond strength of the samples prepared by laser and bur. These results are in contrast to the results of studies by Torres et al, 19 Bahrololoomi et al 18 and Monghini et al 20 who observed lower bond strength of composite to laser prepared primary tooth dentin.…”
Section: Discussionmentioning
confidence: 68%